Effect of Abdominal Circumference on the Irradiated Bowel Volume in Pelvic Radiotherapy for Rectal Cancer Patients: Implications for the Radiotherapy-Related Intestinal Toxicity - Wang, Gang; Wang, Wenling; Jin, Haijie; Dong, Hongmin; Chen, Weiwei; Li, Xiaokai; Bai, Saixi; Li, Guodong; Chen, Wanghua; Li, Leilei; Chen, Juan (Frontiers in Oncology, 2022)
Background To effectively reduce the irradiated bowel volume so as to reduce intestinal toxicity from pelvic radiotherapy, treatment in the prone position with a full bladder on a belly board is widely used in pelvic radiotherapy for rectal cancer patients. However, the clinical applicable condition of this radiotherapy mode is unclear. The aim of this study was to preliminarily identify patients who were not eligible for this radiotherapy mode by analyzing the effect of abdominal circumference on the irradiated bowel volume. Methods From May 2014 to September 2019, 179 patients with locally advanced rectal cancer were retrospectively reviewed in our center. All patients received pelvic radiotherapy. Weight, height, AC, and body mass index (BMI) were used as the research objects, and the irradiated bowel volume at different dose levels (V10, V20, V30, V40, V50) was selected as the outcome variable. Multivariate linear regression and sensitivity analyses were used to evaluate the correlation between AC and irradiated bowel volume. Generalized additive model (GAM) and piecewise linear regression were used to further analyze the possible nonlinear relationship between them. Results Among the four body size indicators, AC showed a negative linear correlation with the irradiated bowel volume, which was the most significant and stable. In adjuvant radiotherapy patients, we further discovered the threshold effect between AC and irradiated bowel volume, as AC was greater than the inflection point (about 71 cm), irradiated bowel volume decreased rapidly with the increase in AC. t-test showed that in patients with small AC (<71 cm), the irradiated bowel volume was significantly higher than that of patients with medium-large AC (≥71 cm). Especially in patients with adjuvant radiotherapy, the mean irradiated bowel volume of patients with small AC was the highest in this study. Compared with adjuvant radiotherapy, in neoadjuvant radiotherapy, the mean difference of irradiated bowel volume between patients with medium-large AC and those with small AC was larger. Conclusion AC is an independent factor influencing the irradiated bowel volume and has a strong negative linear correlation with it. Patients with small AC may not benefit from this common mode of radiotherapy, especially in adjuvant radiotherapy.